CONSUMER LEGAL PROTECTION IN STANDARD AGREEMENTS: A SYSTEMATIC LITERATURE REVIEW OF CIVIL LAW RESEARCH IN INDONESIA - Christian Daniel Hermes; Imman Yusuf Sitinjak (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2025)
Standard-form contracts are contractual instruments widely used in relationships between business actors and consumers because they provide efficiency and legal certainty. However, the practice of standard-form contracts often raises issues of legal protection due to the imbalance of bargaining power between the parties. This article aims to systematically analyze the development of studies on consumer legal protection in standard-form contracts based on civil law research in Indonesia. The method employed is a Systematic Literature Review (SLR) by examining national journal articles published during the period 2015–2024 and indexed in Google Scholar, Garuda, and SINTA databases. The literature selection process followed the PRISMA principles and was analyzed using a thematic approach. The findings indicate that research on consumer legal protection in standard-form contracts has increased, yet remains dominated by normative juridical approaches. The most frequently discussed themes include the imbalance of bargaining power, standard clauses that disadvantage consumers, and the limitation of the principle of freedom of contract. Meanwhile, empirical studies and discussions concerning standard-form contracts in digital transactions remain relatively limited. This study concludes that consumer legal protection in standard-form contracts constitutes a structural issue in civil law, requiring the strengthening of empirical approaches and the adaptation of legal frameworks to the dynamics of modern transactions.